Faktor-Faktor Yang Berhubungan Dengan Kejadian PreEklamsia Di Ruang Camar II RSUD Arifin Achmad Provinsi Riau. - Fitriani, Risa (Jurnal Martenity and Neonatal, 2017)
Preeclampsia is a set of symptoms that occur in pregnant women, maternal and childbirth consisting of hypertension, edema and proteinuria that appear in pregnancies 20 weeks until the end of the first week after childbirth. Factors associated with preeclampsia include age, parity, genetics, twin pregnancy, past disease history (cyclical hypertension, diabetes, kidney disease, and obesity). This study aims to determine the factors causing the incidence of preeclampsia in hospitals Arifin Achmad Riau Province Year 2015. This type of research is quantitative analytical research, with research design used is casse control, with retrospective approach study. Population in this research is all mother mother in room gull II RSUD Arifin Achmad Riau Province Year 2015 with amount of population as many as 1250 childbirth. Univariate and bivariate data analysis using chi square. The result of this study found that there was no correlation between age factor and the incidence of preeclampsia (p = 0,243), there was no correlation between parity factor and preeclampsia (p = 0,659), there was significant correlation between hereditary factor with preeclampsia (p = 0,001) , There was a significant relationship between past history of disease and the incidence of preeclampsia (p = 0.047). It was concluded that there was no significant correlation between age, parity, and occurrence of Preeclampsia, there was a significant relationship between hereditary factors, past history of disease with the occurrence of Preeclampsia